Tuerto Masculinity and Feminine Foresight: Gender and Sight in Ercilla's La Araucana. - Newman, Mary Katherine (Hispanic Review)
This article examines how Alonso de Ercilla's epic poem La Araucana (1569–1590) presents gender through the motif of sight. It argues that Ercilla develops what could be termed tuerto masculinity : a heroic blindness in which male warriors' ocular injuries expose their limited understanding of the Arauco War. In contrast, Indigenous female figures such as Tegualda, Guacolda, and Fresia possess prophecy and foresight that allow them to perceive the conflict's human cost. Drawing on early modern theories of vision, particularly Neoplatonism, the study shows how Ercilla links sight to knowledge and power, making the eye a site where gendered experience and imperial ideology converge. By opposing the blindness of his warriors to the foresight of his heroines, La Araucana reveals that the true tragedy of the Arauco War lies not in defeat but in the failure to see beyond it. This article examines how Alonso de Ercilla's epic poem La Araucana (1569–1590) presents gender through the motif of sight. It argues that Ercilla develops what may be termed tuerto masculinity: a heroic blindness in which male warriors' ocular injuries expose their limited understanding of the Arauco War. In contrast, Indigenous female figures such as Tegualda, Guacolda, and Fresia possess prophecy and foresight that allow them to perceive the conflict's human cost. Drawing on early modern theories of vision, particularly Neoplatonism, the study shows how Ercilla links sight to knowledge and power, making the eye a site where gendered experience and imperial ideology converge. By opposing the blindness of the warriors to the foresight of the heroines, La Araucana reveals that the true tragedy of the Arauco War lies not in defeat but in the failure to see beyond it.